ANALYSIS OF RISK AND RETURN OF FOREIGN EXCHANGE PORTFOLIOS - B12111028, Dahrul Efendi (Jurnal Manajemen Update, 2015)
The market for foreign exchange is the most heavily traded of all financial market.The aims of this study is to analyze the risk and return of the foreign exchanges andto construct an optimal portfolio by Markowitz’s model. For this purpose, themonthly average return of 8 hard currencies against both USD and IDR asreference currencies for the years of 2010 to 2014 have been considered. Theoptimum portfolio of foreign exchanges against USD only consists of CHF, givingthe return of 0.122% and it has standard deviation of 2.634%. While, the optimumportfolio of foreign exchanges against IDR consists of GBP and CHF, giving thereturn of 0.699% and it has standard deviation of 2.248%. The findings of thisstudy will be useful for investors in investment strategy, particularly on foreignexchange market.Key words: Portfolio optimization, Markowitz’s model, Foreign exchanges market